Post‐metamorphic growth partially compensates for the effects of climate‐driven stressors on juvenile frog performance - Laura A. Brannelly; Michel E. B. Ohmer; Lydia Zimmerman; Trina M. Wantman; Phoebe L. Reuben; Jakub Zegar; Samantha S. Fontaine; Molly C. Bletz; Brandon C. LaBumbard; Matthew D. Venesky; Rebecca L. Cramp; Douglas C. Woodhams; et al. (Ecosphere)
Abstract Human‐induced climate change, land use changes, and urbanization are predicted to dramatically impact landscape hydrology, which can have devastating impacts on aquatic organisms. For amphibians that rely on aquatic environments to breed and develop, it is essential to understand how the larval environment impacts development, condition, and performance later in life. Two important predicted impacts of climate change, urbanization, and land use changes are reduced hydroperiod and variable larval density. Here, we explored how larval density and hydroperiod affect development, morphology, physiology, and immune defenses at metamorphosis and 35 days post‐metamorphosis in the frog Rana pipiens. We found that high‐density larval conditions had a large negative impact on development and morphology, which resulted in longer larval periods, reduced likelihood of metamorphosis, smaller size at metamorphosis, shorter femur to body length ratio, and reduced microbiome species evenness compared with animals that developed in low‐density conditions. However, animals from the high‐density treatment experienced compensatory growth post‐metamorphosis, demonstrating accelerated growth in body size and relative femur length compared with animals from the low‐density treatments, despite not “catching‐up” in size. We also observed an increase in relative gut length and relative liver size in animals that had developed in the high‐density treatment than those in the low‐density treatment, as well as higher bacterial killing ability, and greater jump distances relative to their leg length across different temperatures. Finally, metabolic rate was higher overall but especially at higher test temperatures for animals that developed under high‐density conditions, indicating that these animals may expend more energy in response to acute temperature changes. While the effects of climate change have direct negative effects on larval development and metamorphosis, animals can increase growth rate post‐metamorphosis; however, that compensatory growth might come at a cost and reduce their ability to cope with further environmental change such as increased temperatures.